2018
DOI: 10.1111/jonm.12667
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the psychological status of Jordanian nurses working with cancer patients

Abstract: Aim This study aims to explore the psychological status of nurses working with cancer patients in Jordan. Background Literature shows that nurses face many stressors in their job, in particular oncology nurses. Some of them have psychiatric illness such as anxiety and depression. Most of the reviewed studies were conducted in developed countries, and none in the Middle East. Method A qualitative descriptive approach was adopted, whereby interviews were conducted with 24 nurses that were selected from the oncol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…Also, Xie et al, (2020), who showed that, higher risk of nurses developing symptoms of depression and stress. The finding is in consistent with other studies (Lai et al, 2020;Basil et al, 2019;Saifan et al, 2019;Cheung & Yip, 2015). It was unforeseen to find that the frequency of depressive symptoms among nurses weren't that low as we expected.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Also, Xie et al, (2020), who showed that, higher risk of nurses developing symptoms of depression and stress. The finding is in consistent with other studies (Lai et al, 2020;Basil et al, 2019;Saifan et al, 2019;Cheung & Yip, 2015). It was unforeseen to find that the frequency of depressive symptoms among nurses weren't that low as we expected.…”
Section: Discussionsupporting
confidence: 93%
“…Stress can cause several emotional and physical problems including dissatisfaction with self, a sense of failure, severe anxiety, tension, frustration and depression (Khodadadi et al, 2016). With help from their administrators, nurses may turn out to be more prepared to counsel specialists such psychologists or therapists, so that, rising aggravations might be found and treated early (Saifan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…[ 11 ] International research has shown that oncology nurses possess greater coping abilities when caring for terminally-ill cancer patients than nonspecialist nurses in cancer care. [ 26 27 ] Nurses in this study were particularly predisposed to emotional instability because they do not have specialized training in oncology nursing. They used terms such as “feelings of depressions”, “being down” “feel very sad” “not emotionally stable” and “sad moments” to describe the emotional and psychological pressure while they are exposed to caring for cancer patients in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…31 years old. Studies have shown [7]that the crowd who age from 20 to 30 has the highest pressure. Shu Zhou et al [8] investigated 364 low-age nurses (average age is 26.5 years old).…”
Section: Influencing Factors Of Clinical Nurse Mental Health Analysismentioning
confidence: 99%
“…; (4) helping and be helped in humanistic; (5) self-defense mechanism, projection and projective identity and the principle of subconscious work in psychoanalysis; (6) the most important thing is to make members learn in group activities and experience group therapy techniques through observation groups behavior of other members, experience mutual help, providing a safe experimental environment to each other. (7) Learning social communication skills from each other, trying to imitate the adaptive behavior and rebuilding rationality cognition.…”
Section: Psychotherapy Treatment Groupmentioning
confidence: 99%